MINERALOGY AND GEOCHEMISTRY OF TRACE ELEMENTS IN BAUXITES: THE DEVONIAN SCHUGORSK DEPOSIT, RUSSIA - Mordberg L.E.; Stanley C.J.; Germann K. (My University, 2001)
Processes of mineral alteration involving the mobilization and deposition of more than 30 chemical elements during bauxite formation and epigenesis have been studied on specimens from the Devonian Schugorsk bauxite deposit, Timan, Russia. Chemical analyses of the minerals were obtained by electron microprobe and element distribution in the minerals was studied by element mapping. Interpretation of these data also utilized high-resolution BSE and SE images. The main rock-forming minerals of the Vendian parent rock are calcite, dolomite, feldspar, aegirine, riebeckite, mica, chlorite and quartz; accessory minerals are pyrite, galena, apatite, ilmenite, monazite, xenotime, zircon, columbite, pyrochlore, chromite, bastnaesite and some others. Typically, the grainsize of the accessory minerals in both parent rock and bauxite is from 1 to 40 µm. However, even within these rather small grains, the processes of crystal growth and alteration during weathering can be determined from the zonal distribution of the elements. The most widespread processes observed are: (1) Decomposition of Ti-bearing minerals such as ilmenite, aegirine and riebeckite with the formation of ‘leucoxene’, which is the main concentrator of Nb, Cr, V and W. Crystal growth can be traced from the zonal distribution of Nb (up to 16 wt.%). Vein-like ‘leucoxene’ is also observed in association with organics. (2) Weathering of columbite and pyrochlore: the source of Nb in ‘leucoxene’ is now strongly weathered columbite, while the alteration of pyrochlore is expressed in the growth of plumbopyrochlore rims around Ca-rich cores. (3) Dissolution of sulphide minerals and apatite and the formation of crandallite group minerals: ‘crandallite’ crystals of up to 40 µm size show a very clear zonation. From the core to the rim of a crystal, the following sequence of elements is observed: Ca → Ba → Ce → Pb → Sr → Nd. Sulphur also shows a zoned but more complicated distribution, while the distribution of Fe is rather variable. A possible source of REE is bastnaesite from the parent rock. More than twelve crandallite type cells can be identified in a single ‘crandallite’ grain. (4) Alteration of stoichiometric zircon and xenotime with the formation of metamict solid solution of zircon and xenotime: altered zircon rims also bear large amounts of Sc (up to 3.5 wt.%), Fe, Ca and Al in the form of as yet unidentified inclusions of 1–2 µm. Monazite seems to be the least altered mineral of the profile. In the parent rock, an unknown mineral of the composition (wt.%): ThO 2 – 54.8; FeO – 14.6; Y 2 O 5 – 2.3; CaO – 2.0; REE – 1.8; SiO 2 12.2; P 2 O 5 – 2.8; total – 94.2 (average from ten analyses) was determined. In bauxite, another mineral was found, which has the composition (wt.%): ThO 2 – 24.9; FeO – 20.5; Y 2 O 5 – 6.7; CaO 2.0; – ZrO – 17.6; SiO 2 – 8.8; P 2 O 5 – 5.4; total – 89.3 (F was not analysed; average from nine analyses). Presumably, the second mineral is the result of weathering of the first one. Although the Th content is very high, the mineral is almost free of Pb. However, intergrowths of galena and pyrite are observed around the partially decomposed crystals of the mineral. Another generation of galena is enriched in chalcophile elements such as Cu, Cd, Bi etc., and is related to epigenetic alteration of the profile, as are secondary apatite and muscovite.
Keywords: bauxite; laterite; weathering; geochemistry; mineralogy; trace elements; leucoxene; crandallite; zircon; xenotime; pyrochlore; galena; Devonian; Paleozoic::Devonian; Палеозой::Девонская